The main trends in the development of primary education in the Republic of Kazakhstan - Abildina, S.K.; Kenenbaeva, M.A. (Вестник Карагандинского университета, 2016)
The article deals with problems of defining field of continuous education. Analyzing the experience of education at primary school in Kazakhstan and abroad the author touched the question of process of primary educa- tion development in our country. In this regard, proposed modernized new draft of the program of primary education in mathematics today were analyzed and the author showed its positive and negative sides. Expected results under the new program are taken into consideration.
Keywords: the content of education; educational content renewal; continuity; primary education; pre-school education and upbringing